2017
DOI: 10.1182/blood-2016-11-750174
|View full text |Cite|
|
Sign up to set email alerts
|

Selective inhibition of nuclear export with selinexor in patients with non-Hodgkin lymphoma

Abstract: • Selective inhibitor of nuclear export compounds are a novel class of XPO1 inhibitors.• Selinexor is safe and efficacious in patients with R/R NHL.Patients with relapsed or refractory (R/R) non-Hodgkin lymphoma (NHL) have a poor prognosis and limited treatment options. We evaluated selinexor, an orally bioavailable, first-in-class inhibitor of the nuclear export protein XPO1, in this phase 1 trial to assess safety and determine a recommended phase 2 dose (RP2D). Seventy-nine patients with various NHL histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
106
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 45 publications
1
106
0
Order By: Relevance
“…1416 In one study, 31% of evaluable patients had an objective response with use of selinexor across a spectrum of non-Hodgkin’s lymphoma subtypes, with a median duration of response exceeding 10 months. 16 In another study, among 157 evaluable patients with advanced or metastatic solid tumors, single-agent selinexor resulted in an objective response rate of 4%, and a stable disease rate of 43%. 17 …”
Section: Nuclear Export Targetingmentioning
confidence: 99%
“…1416 In one study, 31% of evaluable patients had an objective response with use of selinexor across a spectrum of non-Hodgkin’s lymphoma subtypes, with a median duration of response exceeding 10 months. 16 In another study, among 157 evaluable patients with advanced or metastatic solid tumors, single-agent selinexor resulted in an objective response rate of 4%, and a stable disease rate of 43%. 17 …”
Section: Nuclear Export Targetingmentioning
confidence: 99%
“…Moreover, objective responses were correlated with improved PFS and OS. 8 In addition, selinexor has demonstrated excellent brain penetration and promising results in both pre-clinical and clinical models of glioblastoma. 9,10 Recently, a phase 2 study in patients with recurrent glioblastoma showed 17% of PR and 33% of stable disease in 12 patients, which confirms its activity in brain tumors.…”
mentioning
confidence: 99%
“…6 Anti-tumor activity of selinexor in DLBCL has recently been demonstrated in phase I trials. 7,8 Moreover, selinexor has shown excellent brain penetration and encouraging efficacy in patients with recurrent glioblastoma. 9,10 Promising results in pre-clinical models of primary CNS lymphoma (PCNSL) have been reported as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleocytoplasmic transport is a highly regulated and coordinated function and involves different nuclear transport factors or receptors, namely, importins and exportins. The inhibition of nucleocytoplasmic transport is an innovative strategy in the treatment of neoplastic diseases, including those with multiple genomic alterations and resistance mechanisms such as tFL . The role of BCL‐2 gene lesions in tFL also suggests that drugs interfering with the overexpression of the gene may represent a therapeutic option in this setting of patients …”
Section: Prognosis and Therapeutic Options At Htmentioning
confidence: 99%